Determinan Pertumbuhan Ekonomi Negara Asean-10: Model Data Panel - Rosnawintang; Dinayati, Lilis; Balaka, Muh. Yani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the effect of investment, exchange rate, labor, and human development index (HDI) variables on economic growth in ASEAN countries. This study uses panel data regression analysis with time series data from 2011-2022 and cross-section data from 10 ASEAN countries. The results showed that the Fixed Effect Model was selected as the best model in the study. The results of the analysis concluded that investment and labor have a positive and significant effect on economic growth and HDI has a negative and significant effect on economic growth. Meanwhile, the exchange rate does not have a significant effect on economic growth. In other words, increasing investment and labor will increase economic growth, conversely if the HDI increases it will not increase economic growth. In addition, the exchange rate has no effect on economic growth in 10 ASEAN countries.